Dynamics of household cooking fuel choices in Cameroon: A comprehensive analysis of the transition from biomass to LPG - Flavian Emmanuel Sapnken; Théodore Patrice Nna Nna; Marcel Rodrigue Ewodo-Amougou; Jean Marie Stevy Sama; Jean Gaston Tamba (Energy Strategy Reviews)
This study investigates the factors influencing the choice of cooking fuels in Cameroon, analyzing trends over two distinct periods (2007–2014 and 2014–2021). Using data from the Cameroonian Household Living Standards Survey and employing the Additive Random Utility Model, the study explores the determinants of household fuel selection, focusing on income, education, household size, and urban/rural demographics. The findings reveal a significant transition from traditional biomass fuels to modern energy sources, particularly liquefied petroleum gas (LPG), driven by government incentives and growing awareness of health and environmental issues. Despite this shift, biomass remains the dominant source of energy, with 76.4 % of households still relying on it for cooking in 2021. Policy recommendations include strengthening poverty alleviation programs, promoting educational campaigns on the health and environmental impacts of biomass, and ensuring the sustainability of LPG adoption through improved supply chains and targeted subsidy mechanisms. This research offers important insights for policymakers in Cameroon and similar contexts in Sub-Saharan Africa, contributing to the literature on household energy choices and energy transitions.